The Education of Perfect Youth of Our Time Should Be the Work of all and Everyone Should be Responsible in it (Eurasian Research Bulletin, 2022)
In this article, an attempt is made to justify the state policy dedicated to the youth problem and the specific changes taking place in this regard. To support the social protection of young people, to hold events related to the formation of national pride and loyalty to the Motherland, to provide comprehensive support to young people in the conditions of the market economy, to organize new jobs for them, to allocate grants for their higher education, to find talented children in our republic and encourage them. - based on reinforcement